Protein-concentration-dependent adsorption behaviour of inorganic layered materials. Issue 15 (25th February 2015) - Chao(Wu), Victor Wei-Keh; Hsu, Chao-Chen; Lu, Wei-Ming; Chen, Wen-Jing; Naveen, Bunekar; Tsai, Tsung-Yen
<x xml:space="preserve">Abstract</x> Adsorption patterns of BSA in different inorganic layered materials with different ionic exchange capacities (IEC) of low, suitable and high are shown from left to right. BSA/Clay concentrations (0/1-5/1) with respective d-spacing are shown from left to right.